Can Social Concern Theory Explain Quarantine-Related Misbehavior During the COVID-19 Pandemic? An Inquiry in the Urban Context of Iran - Kabiri, Saeed (Crime & delinquency, 2024)
The COVID-19 pandemic has precipitated quarantines in many urban settings, and rules have been enforced to ensure that citizens are complying with health-related mandates. However, anecdotal and empirical evidence confirm the prevalence of policy transgressions. Non-compliance with COVID-19 mandates can have severe consequences for individual health, societal fear, and the global economy. Thus, it is important to better understand the etiology of such misbehavior in the hopes of ensuring policy adherence. Using Agnew?s social concern theory as a conceptual framework, this study investigates quarantine-related misbehavior in the urban context of Rasht, Iran. Survey data of 393 university students indicate that social concern theory can explain quarantine-related misbehavior. Specific findings, implications, limitations, and directions for future research are discussed.